Questioning theoretical primitives in linguistic inquiry papers in honor of Ricardo Otheguy - Shin, Naomi Lapidus; Erker, Daniel (Daniel Gerard); Otheguy, Ricardo, 1945- (Studies in functional and structural linguistics (SFSL),, 2018)
"Across the world, professional linguistic inquiry is in full bloom, largely as result of pioneering thinkers who helped rapidly modernize the study of human language in the last century. As the field continues to move forward, further solidifying its position as a conduit of insight into the human condition, it is essential to take stock of the theoretical primitives that have given linguistics its intellectual foundation. This volume does precisely that, inspecting the load-bearing components of the edifice upon which contemporary linguistics has been constructed"--